KAJIAN ANTROPOLOGI SASTRA DAN NILAI PENDIDIKAN KARAKTER RELIGIUS DALAM PANTUN ADAT JAMBI SERTA RELEVANSI DENGAN PEMBELAJARAN SASTRA DI SMP - Sampoerno, Mohd. Norma; Sumarlam, Sumarlam; Suyitno, Suyitno (Jurnal S2 Pendidikan Bahasa Indonesia, 2016)
This study contains about the complexity of ideas, the complexity of the activity, and the complexity of culture results, religious character of the educational value that is contained in Jambi traditional poem and the relevance to learning literature in junior high school. This study is a qualitative research, using descriptive analytic method, the data in this study is the review of documents Jambi traditional poem. Sources of data in this study is divided into two secondary data and primary data. Sources of primary data in this study a textbook poem in Jambi traditional poem book. Secondary data sources in this study is the source of the data obtained from informants, journal, books and research relevant to literary anthropology. Data collection techniques used in this research is documentation and depth interviews with informants. The validity of the data using data triangulation and triangulation theory. The analysis technique using an interactive model. The results of this study indicate the complexity of ideas, activities and culture results in Jambi traditional poem; found the values of the religious character education contained in Jambi traditional poem, it is appropriate when used as teaching materials of literary study in junior high school, because the values of character education that can be applied to everyday life and it has relevance in terms of language. The language used in Jambi traditional poem was an easy language to understand by students because it uses everyday language, if there are any special term local Jambi language, therefore in Jambi traditional poem There are explanations intent of the language that difficult to understand.